1991
DOI: 10.1149/1.2085536
|View full text |Cite
|
Sign up to set email alerts
|

Metalorganic Surface Chemical Adsorption Deposition of AlN Films by Ammonia and Trimethylaluminum

Abstract: Experiments were carried out to investigate the feasibility of metalorganic surface chemical adsorption deposition (MOSCAD) for growing aluminum nitride (A1N). This technique tends to promote only surface reactions, confining the decomposition, interactions between intermediates and deposition processes necessary for crystal growth to the substrate surface. As a result, low-temperature deposition becomes possible. Epitaxial A1N growth was demonstrated at a temperature as low as 400~ The A1N film, grown at a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Under the condition eliminating any present moisture, the AlCH x radicals with dangling bonds generated by the TMA decomposition survives and contributes to film growth as discussed in the previous report (the second panel of Fig. 1(c)) [15].…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Under the condition eliminating any present moisture, the AlCH x radicals with dangling bonds generated by the TMA decomposition survives and contributes to film growth as discussed in the previous report (the second panel of Fig. 1(c)) [15].…”
Section: Resultssupporting
confidence: 55%
“…MOCVD processes below the NH 3 decomposition temperature are also possible via the surface reaction. The heterogeneous decomposition of TMA starts to appear at 300 • C [14,15]. When TMA thermally decomposes on the surface, it tends to produce dangling bonds, such as AlCH 2 , AlCH 3 , and AlCH radicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that NH 3 decomposes on the surface by reaction with TMIn or its decomposition products [28][29][30]. So, there is a compromise in obtaining the optimum V/III molar ratio, since the injected ammonia must be large enough to permit InN growth, but must not result in an excess amount of H 2 , which will ''etch'' the layer.…”
Section: Inn Filmsmentioning
confidence: 99%
“…AlC13-NH3. Recently, Yu et al [2] demonstrated that in the Al(CH3)3 -NH3 CVD process the growth temperature can be lowered down to 400 "C by confining all the film forming reactions on the substrate surface, thus eliminating possible gas phase reactions including the adduct formation. Likewise, Asif Khan et al [3] reported that while temperatures exceeding 700 "C were needed in a conventional CVD to grow epitaxial AlN films from Al(C2H5)3 and NH3, the Atomic Layer Epitaxy (ALE) technique was capable of producing films with a high quality already at 450 "C. As distinct from CVD, in ALE the precursors are led onto the substrate alternately [4,5].…”
Section: Introductionmentioning
confidence: 99%